(untitled) (مجلة المنصور, 2022)
One of the most important issue in networking is the tremendous demand for a huge bandwidth with a great security. Optical network is an efficient telecommunications networks used to transfer data with great facilities. To provide an additional capacity for higher bandwidth, different frequencies and longer distance, optical Dense Wavelength Division Multiplexing (DWDM) and Erbium-Doped Fiber Amplifiers (EDFA) will be used. To transfer data securely, an important encryption method RC4 will be used to protect data on the common channel as it’s cryptographic technique is faster, simpler to implement and the keystream is a arbitrary sequence of bits which guarantees the security of used cipher. MATLAB program will used to encrypt and decrypt the image with transferring it optically by Optisystem simulation program.